THE PSYCHOLOGICAL EFFECTS OF SLAVERY IN TONI MORRISON’S BELOVED - Suswanti Higinik; Elisabeth Z Oroh; Tirza A Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This research aims to reveal the psychological effects of slavery in Toni Morrison’s Beloved, especially depression and feeling of insecure. This research is qualitative research because the data that support this research are collected from books, journals, articles, and internet. Data collection is taken in two forms namely the primary source that is the novel itself and secondary sources are books, articles, the internet and journals. To analyse the data of this research, the writer uses psychological approach, which studies the behaviour of human life. Based on the results of research, it is shown that there are some psychological effects of slavery concerning living life full of depression and insecure, that are feeling of sadness, helplessness, worthlessness, fear, hopelessness and uncertainty.